California State College at Hayward nineteen sixty four - nineteen sixty five General Bulletin - California State College, Hayward:::::: (1964)
A catalog of courses offered by California State College at Hayward for the academic year 1964-1965. Includes academic calendar, history of the college, names of faculty and administrators, and descriptions of courses and degrees offered.